Effect of thiourea on structure, morphology, and optical properties of spray deposited CZTS thin films for solar cell applications - Ramesh B. Mahewar; Ravikumar R. Vidule; Limbraj S. Ravangave (Institute of Advanced Engineering and Science, 2021)
Cu2ZnSnS4 (CZTS) films of different Thiourea (SC (NH2)2) molarity were deposited by using a simple chemical spray technique at substrate temperature 275 °C. Analytical reagent Grade Copper chloride (CuCl2), Zinc chloride (ZnCl2), and Tin chloride (SnCl4.5H2O) were used as Cu+, Zn+, and Sn+ ion sources respectively and thiourea (SC(NH2)2) (0.02, 0.04, 0.06, 0.08, and 0.1 M) was used as an S- ion source. A set of five CZTS films was deposited using five different molarity of thiourea. The structure, morphology, elemental analysis, and optical properties of these films were studied using X-ray diffractometer (XRD), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), and UV-visible spectroscopy techniques respectively. The XRD spectra showed that all films are polycrystalline tetragonal structures with preferential orientation along 112 planes. The calculated crystallite size was increased with an increase in thiourea concentration. Variations of optical band gap with thiourea molarity have been investigated using Tauc plots. SEM micrographs exhibit CZTS spherical granules regularly arranged with some void spaces. The purity of deposited films was investigated using EDX analysis. All the CZTS films exhibit a higher absorption coefficient (α>104) cm-1 and a band gap in the reported range (1.2 to 1.53 eV) can be used as an absorber layer in solar cells.